The Implementation of the Balanced Scorecard in the Target Setting Aspect for Building Public Interest - Mohammad Kanzul Fathon; Agus Eko Sujianto; Sulistyorini Sulistyorini (International Forum of Researchers and Lecturers, 2025)
This study is motivated by the current need for research on pesantren management using the Balanced Scorecard approach, which is essential to identify areas that require improvement in order to increase public interest. Innovative institutions have the opportunity to adopt the Balanced Scorecard as a strategic management system for managing long-term strategies. The research employs a qualitative method and was conducted at Pondok Pesantren Anharul Ulum Soko Plumpungrejo Kademangan Blitar and Pondok Pesantren Bustanul Mutaallimat Dawuhan Kauman Kepanjen Kidul in Blitar City. Data collection techniques include participant observation, in-depth interviews, and documentation. Data analysis techniques involve data condensation, data display, and conclusion drawing or verification. The findings reveal that target setting to build public interest is carried out through several measures. First, institutional development involves transforming pesantren from a salafi model into an integrated institution equipped with formal education facilities. This transformation includes requiring students to reside on-site and implementing strict selection processes to maintain the quality of the pesantren. Additionally, programs and curricula are designed to align with community needs by considering feedback from prospective students' parents, many of whom desire a combination of formal education, pesantren learning, and Quran memorization. Furthermore, the performance of pesantren in building public interest is measured through four perspectives: financial perspective, customer satisfaction perspective, internal business process perspective, and growth and learning perspective.